Humpback Highs and Lows Amid Shifting Seas and a Northeast Pacific Marine Heatwave: Whale Demographics in the Main Hawaiian Islands, 2002–2023 - S. M. Barber‐Meyer; T. Cheeseman; J. Barlow; L. Bejder; A. L. Bradford; R. Cartwright; M. Deakos; L. Evans; R. Finn; C. M. Gabriele; B. Goodwin; C. Hayslip; et al. (Marine Mammal Science, 2026)
North Pacific humpback whales are a celebrated conservation success, rebounding from extensive commercial whaling. Yet they remain vulnerable to the impacts of climate change, a multifaceted stressor that can exacerbate existing threats. During 2013–2016, a Northeast Pacific marine heatwave severely reduced forage availability in their feeding grounds, concurrent with diminished whale recruitment and increased mortality. We analyzed photo‐identification data of whales that visited the Main Hawaiian Islands from 2002 to 2023 to estimate apparent survival, abundance, and distinct population segment (DPS) growth rates. Survival was high prior to (0.987; SE = 0.003), low during (0.684; SE = 0.022), and higher, but still reduced, after (0.956; SE = 0.006) the heatwave. Annual breeding season abundance estimates averaged 11,617 (SD = 1914) and included a striking 37% decrease from 2014/15 to 2021/22. While the average annual DPS growth rate was stable (1.00) over 20 breeding seasons, shorter periods included high growth (1.09) and steep decline (0.783). Depressed survival and abundance estimates may signal lingering heatwave effects or adjustment to current carrying capacity. Climate change predictions include more frequent, intense, and longer heatwaves; thus, this DPS serves as a crucial ecosystem‐health indicator. Continued research and monitoring are essential to support resiliency against future climate perturbations.